Electromyography features information based on functional range of motion for health screening program - Saad, Norhashimah Mohd; Zawawi, Tengku Nor Shuhada Tengku; Abdullah, Abdul Rahim; Sudirman, Rubita (2023)
Musculoskeletal disorders (MSDs) are the most common cause of illnesses in the industrial sector. In Malaysia, injured workers from the industry are allocated at the Social Security Organization (SOCSO) Rehabilitation Centre to monitor the injuries and analyze the patients who are able to retain work. However, the screening process has the disadvantage of efficiency since the results are obtained manually based on the instructor's observation rather than providing objective assessment. Electromyography (EMG) pattern recognition is a promising rehabilitation strategy that may enhance muscular function's observation. This study investigates EMG signal's behavior of left and right biceps brachii while using a functional range of motion (FROM) for health screening program (HSP). Two activities which are axial rotational reach and upper-level reach were evaluated. The findings indicate that the right biceps brachii is tend to have higher muscle performance compared to the left biceps and the force of the right and left biceps is greater during the axial rotational reach than upper-level reach activity. The results of this study will assist rehabilitation centers in evaluating the performances of their patients. These features information can be used as indicators for screening patients treated in rehabilitation centers that needs further rehabilitation program or retain to work.